ASSESSMENT OF MICROBIAL LOAD OF RAW MEAT AT ABATTOIRS AND RETAIL OUTLETS - M. U. D. Ahmad; A. Sarwar M. I. Najeeb; M. Nawaz; A. A. Anjum; M. A. Ali; N. Mansur (Journal of Animal and Plant Sciences, 2013)
Aim of the present study was to assess the microbial load of raw meat at abattoirs and retail outlets in different areas of Lahore. Beef, mutton (sheep, goat) and chicken meat samples (n=140) were collected from various abattoirs (n=60) and retail outlets (n=80). All the samples were subjected to aerobic plate count (APC), E. coli count, Staphylococcus aureus count and Salmonella detection. Mean APCs of beef, sheep, and goat meat from abattoirs (5.35, 5.42 and 4.84 log10 CFU/cm2 respectively) were significantly lower as compared to APC values of retail outlets (7.15, 6.92 and 6.62 log10 CFU/cm2 respectively). Mean APC of chicken meat from retail outlets was 7.22 log10 CFU/cm2 . Mean E. coli counts for the beef, sheep and goat meat from abattoirs and retail outlet were 2.81, 2.94; 2.64, 2,78 and 2.86, 1.94 log10 CFU/cm2 respectively, while mean S. aureus counts were 2.76, 2.91; 2.90, 2.96 and 2.80, 3.07 log10 CFU/cm2 respectively. Mean E. coli and S. aureus counts for chicken outlets were 2.74 and 3.80 log10 CFU/cm2 , respectively. There were no significant differences (p ≤ 0.05) between the E. coli and S. aureus number for the abattoirs and retail outs of beef, sheep and goat meat. The E. coli, S. aureus and Salmonella were detected from total of 45%, 72% and 26% samples respectively. It is concluded that microbial load of raw meat from abattoirs and retail shops in Lahore is high which insinuates its possible role in spoilage and food-borne illnesses.
Keywords: Meat; Abattoir; Retail outlets; E. coli; Staphylococcus aureus and Salmonella